El oppidum de la Ulaña en la frontera meridional de los cántabros (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
We make some considerations taking into account the data provided by the excavations in La Ulaña site and some of its features: stretch of land, geographical location, building materials and structures. So we try to dwell on the sort of settlement and the influence over, due to its bordering context, the culture between the Cantabrian and the North Meseta peoples.